SNP-Based Genome-Wide Association Mapping of Pollen Viability Under Heat Stress in Tropical Zea mays L. Inbred Lines - Ahmed, Zubair; Khalid, Maria; Ghafoor, Abdul; Shah, Muhammad Kausar Nawaz; Raja, Ghazala Kaukab; Rana, Rashid Mehmood; Mahmood, Tahir; Thompson, Addie M. (Frontiers in Genetics, 2022)
Global environmental changes with more extreme episodes of heat waves are major threats to agricultural productivity. Heat stress in spring affects the reproductive stage of maize, resulting in tassel blast, pollen abortion, poor pollination, reduced seed set, barren ears and ultimately yield loss. As an aneamophelous crop, maize has a propensity for pollen abortion under heat stress conditions. To overcome the existing challenges of heat stress and pollen abortion, this study utilized a broad genetic base of maize germplasm to identify superior alleles to be utilized in breeding programs. A panel of 375 inbred lines was morpho-physiologically screened under normal and heat stress conditions in two locations across two consecutive planting seasons, 2017 and 2018. The exposure of pollen to high temperature showed drastic decline in pollen germination percentage. The average pollen germination percentage (PGP) at 35°C and 45°C was 40.3% and 9.7%, respectively, an average decline of 30.6%. A subset of 275 inbred lines were sequenced using tunable genotyping by sequencing, resulting in 170,098 single nucleotide polymorphisms (SNPs) after filtration. Genome wide association of PGP in a subset of 122 inbred lines resulted in ten SNPs associated with PGP35°C (p≤10-5), nine with PGP45°C (p≤10-6-10-8) and ten SNPs associated with PGP ratio (p≤10-5). No SNPs were found to be in common across PGP traits. The number of favorable alleles possessed by each inbred line for PGP35°C, PGP45°C, and the PGP ratio ranged between 4-10, 3-13 and 5-13, respectively. In contrast, the number of negative alleles for these traits ranged between 2-8, 3-13 and 3-13, respectively. Genetic mapping of yield (adjusted weight per plant, AWP-1) and flowering time (anthesis-silking interval, ASI) in 275 lines revealed five common SNPs: three shared for AWP-1 between normal and heat stress conditions, one for ASI between conditions, and one SNP, CM007648.1-86615409, was associated with both ASI and AWP-1. Variety selection can be performed based on these favorable alleles for various traits. These marker trait associations identified in the diversity panel can be utilized in breeding programs to improve heat stress tolerance in maize.